Analysing the effect of trading characteristics on liquidity measures – a combined approach to liquidity: evidences from Tehran Stock Exchange. (10th March 2020) - Fathi, Saeed; Jalali, Somaye; Ajam, Alireza; Sadeghi, Omid Mirmohammad
Liquidity estimation has always been of conspicuous importance to all investors as well as risk and return. The purpose of this study is to examine the impact of trading characteristics (price, trading volume, variability, return volatility, absolute stock return, and Beedles thin trading measure) on liquidity measures (Amihud illiquidity ratio, return reversal measure, stock turnover, zero return, turnover-volatility ratio and proportional bid-ask spread) in Tehran Stock Exchange. We extend previous studies by combining different liquidity measures using TOPSIS technique and by employing a multidimensional variable, namely TOPSIS output. Results reveal both of the liquidity measures are strongly related to trading characteristics including stock turnover and zero return. Also, stock price, trading volume, and Beedles thin trading measures are the most significant factors in estimating liquidity. Different effects of different liquidity measures indicate that liquidity is a multidimensional and complex concept, and each measure reflects only one aspect of liquidity. The results of examining the influence of trading characteristics on the combined (multidimensional) liquidity measure indicate that trading characteristics are the main determinants of liquidity.